High Participation, Low Impact: The Challenge for Teacher Professional Development in Indonesia - Abdul Rahman (International Journal of Pedagogy and Teacher Education, 2021)
The present study investigates teacher professional development (TPD) experiences from three different schools in regional Indonesia. A case study design is adopted and a questionnaire and a semi-structured interview are administered to collect data about professional development experiences of teachers, highlighting teachers’ participation and perceived impacts of TPD on their instructional practices. The collected data are quantitatively and qualitatively analysed to see trends and patterns of teachers’ TPD practices. The findings of this study problematise the teachers’ high level of TPD participation but low impact of TPD on teachers’ instructional practices. Some key findings and practical recommendations that are likely to help teachers to translate TPD ideas into their day-to-day practices are discussed and put forward.